INTEGRATED devices in MIR for on chip applications - shafaay, sara ahmed (AUC Knowledge Fountain, 2019)
Gas sensing play an important role in various fields such as environmental, medical, and for industrial applications. A precise controlling for the mount of a gas in certain place can be vital in quality for industrial process, for security, and for human health applications. Selectivity , sensitivity, and foot print are the main characteristics in designing any gas sensors. We chose to work in mid-infrared (MIR) because it contains special peaks for each type of gas which help improve the selectivity for any gas sensor. Mid-infrared (MIR) region is an important region for sensing applications because it contains vibrational resonance for many gases such as methane, carbon monoxide, carbon dioxide, sulfuric acid, ammonia, and acetone. Doped silicon with negative permittivity in MIR region can be used in plasmonic technology to design gas sensors which combining both benefits of silicon and plasmonic technology in MIR region. Fabricating plasmonic integrated devices became easier with current progress in Nanotechnology. Small foot print could be achieved by using Plasmonics technology. In this thesis, we introduce various novel integrated optical gas sensors. These optical gas sensors determine the change in refractive index of the surrounding. Optical gas sensing method is chosen because it is rapid, reliable, and highly sensitive method. We chose to design a slotted ring resonator and stub resonator to detect various types of gases. However, it is very difficult to detect certain types of gases because they are colorless, odorless, and tasteless gas such as methane, carbon monoxide and carbon dioxide. Methane gas is main source of a fuel and it causes climate changes; Carbon dioxide has many economic uses such as enhancing oil recovery and extracting caffeine from coffee. Carbon dioxide uses in food industry, chemical industry, and oil industry and used in safety application such as fire extinguisher. FDTD simulation is used in designing both the ring resonators, stub filter and fabry-perot resonators. The doping level is responsible for indicating the value of the plasma resonance. Drude model is used to define Silicon with high dopant level and the permittivity, resonance frequency, and plasma collision are calculated. while, for the gases we used the absorption data from NIST (National institute of standards and technology) data base that relates the absorption coefficient Î± (Î») with the wavelength in MIR. Consequently, the extinction coefficient k (Î») is calculated from Kramers-Kronig relation, so the refractive index n (Î») could be predicted. The refractive index data verses the wavelength is fitted by using Lumerical FDTD simulation. First, we studied the behavior for doped silicon waveguide and its dispersion curve. Furthermore, we studied the relation between the attenuation constant and the wavelength. novel doped silicon structures were introduced. We proposed a stub and a fabry-perot resonators. Sensitivity, quality factor, and figure of merit were studied. Secondly, we studied the response of ring resonators gas sensor and calculate its sensitivity and we calculate both the quality factor and the figure of merit. A comparison between air transmission line and methane and carbon dioxide transmission lines was done. Furthermore, we studied the behavior of two rings coupled with the waveguide, two coupled rings coupled with straight waveguide, and two coupled rings coupled with 90 degrees bending waveguide resonators. We designed a stub filter with different heights which causes wavelength shifting. Finally, we tried to use the resonance splitting phenomena. We introduce two nested ring resonators have the same resonance wavelength inside each other and coupled with straight waveguide. We used this phenomenon in two different wavelengths ranges, the MIR and NIR range. Furthermore, we achieved a high sensitivity up to 18146nm/RIU.